Annelerin Bakış Açılarından Salgın Sürecinde Sınava Hazırlanma - Bakiler, Esra; Türk Kurtça, Tuğba (Muş Alparslan Üniversitesi, 2021)
The purpose of this study is to examine the experiences of students preparing for the High School Entrance Exam (LGS) during the pandemic period from the perspective of mothers. The research was planned in generic qualitative research design. The data were collected through interviews with eleven participants on online platforms. A semi-structured interview form was used in the interviews. The results of the research indicate the positive and negative effects of changing conditions during the pandemic period in areas such as learning and inter-family relationships. Research findings also point to concerns brought on by uncertainty, the increase in support needs from different sources and increased risks in certain areas.

Bu çalışmanın amacı, salgın döneminde Lise Giriş Sınavı'na (LGS) hazırlanan öğrencilerin deneyimlerini anneler açısından incelemektir. Araştırma, genel nitel araştırma deseninde planlanmıştır. Veriler, çevrimiçi platformlarda on bir katılımcıyla görüşülerek toplanmıştır. Görüşmelerde yarı yapılandırılmış görüşme formu kullanılmıştır. Araştırma sonuçları, salgın döneminde değişen koşulların öğrenme ve aile içi ilişkiler gibi alanlarda olumlu ve olumsuz etkilerini göstermektedir. Araştırma bulguları, belirsizliğin getirdiği endişelere, farklı kaynaklardan gelen destek ihtiyaçlarının artmasına ve belirli alanlarda artan risklere de işaret etmektedir.
Preparing for Exam during the Pandemic Period from the Perspective of Mothers
anemon
Keywords: pandemic; distance education; school-family relationship; parent involvement; High school entrance exams; school guidance services; Salgın; uzaktan eğitim; ebeveyn katılımı; sınava hazırlık; liseye giriş sınavı